Considerações psicanalíticas sobre o trauma: da repetição há simbolização? - Stamford, Rafael Esteves (2025)
The work is presented in a context in which the author's clinical practice draws his attention to the issue of trauma, repetition and symbolization: inseparable concepts, encompassing what he calls “pathologies of acting”, understanding them as a “non-integration” of the traumatic experience. To this end, three chapters have been put together to meet the general objective of the work based on the specific objectives. The general objective is to analyse the relevance of the concepts of trauma, repetition and symbolization from the perspective of Freud and René Roussillon. With this in mind, specific objectives were set: 1- to study the evolution of Freudian theory on trauma and repetition from “Neurosis” (1895) to the notion of originary trauma (1926); 2- to understand the place of symbolization in the processes of subjectivation based on René Roussillon's thinking; 3- to show how these concepts are presented through the study of two works of fiction. Thus, the concepts of trauma and repetition throughout Freud's work were worked on using selected texts that shared the theme and increased the discursive value of the dissertation. Subsequently, Ferenczian concepts that complement Freud's were explained in order to give more support to the theory of psychoanalysis. Based on Freud's ideas, the notions of primary and secondary symbolization and primary and secondary trauma were also presented, which were coined from the perspective of the French psychoanalyst René Roussillon, who dealt substantially with narcissistic-identity suffering. As a result, it was possible to analyze two works of fiction: one literary and the other audiovisual. However, before that, we reflected on the era in which psychoanalysis was founded and the analyst's stance towards a modern society, which produces its own subjectivities. Nowadays, with the expansion of psychoanalytic theory, new sufferings can be encompassed by analytic treatment, but leading the analyst to change their classic stance towards these new psychopathologies, such as narcissistic-identity sufferings. At the end of the work, we reflected on the importance of research for both the clinic and the academic world, since we talk about what are called “difficult cases” and how the analyst's management can help those who suffer during their process, but also leaving the research open to questioning and new directions based on what has been presented.